DA-9701 on gastric motility in patients with Parkinson's disease: A randomized controlled trial. (September 2018) - Shin, Cheol Min; Lee, Yoon Jin; Kim, Jong-Min; Lee, Jee Young; Kim, Kyung-Joon; Choi, Yoon Jin; Kim, Nayoung; Lee, Dong Ho
Abstract: Introduction: To evaluate the effect of DA-9701, a novel prokinetic drug, on gastric motility evaluated by magnetic resonance imaging in patients with Parkinson's disease (PD). Methods: Forty PD patients were randomly allocated to receive either domperidone or DA-9701. Their gastric functions were evaluated using magnetic resonance imaging before and after 4-week treatment period. Information on levodopa daily dose, disease duration, and Unified PD Rating Scale scores was collected. In 18 patients (domperidone: 9, DA-9701: 9), plasma levodopa concentrations were determined. Primary outcome was assessed by a one-sided 95% confidence interval to show non-inferiority of DA-9701 vs. domperidone with a pre-determined non-inferiority margin of -10%. Results: Thirty-eight participants (19 men and 19 women; mean age, 67.1 years) completed the study protocol (domperidone: DA-9701 = 19:19). Gastric emptying rate at 120 min (2-hr GER) was comparable between the 2 groups; it was not correlated with levodopa daily dose or disease duration or Unified PD Rating Scale scores (all p  > 0.05). DA-9701 was not inferior to domperidone in changes of 2-hr GERs before and after the treatment (absolute difference, 4.0 %; one-sided 95% confidence interval, – 3.7 to infinity). However, a significant increase in 2-hr GER was observed only in DA-9701 group (54.5% and 61.8%, before and after treatment, respectively, p  < 0.05). Plasma levodopa concentration showed an insignificant but increasing trend in DA-9701 group. There were neither adverse reactions nor deteriorations of parkinsonian symptoms observed in the study participants. Conclusion: DA-9701 can be used for the patients with PD to enhance gastric motility without aggravating PD symptoms (ClinicalTrials.gov number:NCT03022201 ). Highlights: Many patients with Parkinson's disease (PD) suffer from a decreased gastric function. We evaluated the effect of DA-9701, a new prokinetic drug, on gastric motility using gastric MRI. Four-week administration of DA-9701 significantly improved gastric emptying rate in PD patients. Furthermore, plasma levodopa concentration showed an increasing trend. Thus, DA-9701 can be used as a safe and effective therapy for PD patients.